HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU ANAK KELAS 3 SDN MALANGJIWAN KECAMATAN COLOMADU KABUPATEN KARANGANYAR - Ningsih, Endang Dwi; Rivanti, Agnes (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Introduction: Parenting parents against children is the interaction between children and parents during the conduct of activities nurture, educate, guide and discipline and protecting the child to reach maturity in accordance with the norms prevailing in society. Family influence in the formation and development of the child's personality is very large because the family is the first social group where children can interact, where children learn and express themselves as social beings.Purpose of the study: was to determine the relationship between parenting parents with a child's behavior.Subjects: were 31 children grade 3 SDN Malangjiwan Colomadu. The sampling technique used is saturated sampling where all subjects are used as the sample. The datas are collected by questionnaire method for a variable pattern of parenting and child behavior, the data were analyzed with Chi Square test. The results were obtained for 0,032 there for p <0.05.Conclusion: of this research is there is a relationship between parenting parents with a child's behavior grade 3 SDN malangjiwan Colomadu. Keywords: Parenting, child behavior